IDENTITY THEFT: ISSUES AND CHALLENGES FROM ISLAMIC FINANCE PERSPECTIVE - Muhammud, Farah Safura; Bakar, Nur Ain Abu (Jurnal 'Ulwan, 2024)
Identity theft is a serious security issue for Malaysians. This study uses a qualitative approach involving an authority and academics to gather their perceptions, information, and solutions regarding identity theft occurring on internet forums. The objectives of the study are as follows: (1) to identify the concept of identity theft; (2) to explain the issue and factor of identity theft; and (3) to analyze the challenges and solutions to identity theft. Apart from that, according to the study's findings, (1) The prevalence of identity theft in Malaysia is on the rise every year, and (2) identity theft can have serious repercussions, including financial losses or the misuse of private and confidential user information to obtain fake documents. This research is hoped to change the way individuals use the internet to decrease the risk that they become fraud victims, and increase their understanding of the numerous issues that cybercrime raises. The government must create comprehensive and successful awareness efforts to Malaysian citizens in order to ensure that the message is received and that they are capable of halting the identification theft in this nation.